Environmental and economic performance of beef farming systems with different feeding strategies in southern Brazil. (July 2016) - Pashaei Kamali, Farahnaz; van der Linden, Aart; Meuwissen, Miranda P.M.; Malafaia, Guilherme Cunha; Oude Lansink, Alfons G.J.M.; de Boer, Imke J.M.
Abstract: Beef production is one of the contributors to emission of pollutants to the environment, and increasingly competes for natural resources. Beef producers can improve their environmental performance by adopting alternative feeding strategies. Adoption of alternative feeding strategies, however, might negatively impact farm profitability. The objective of this study was to evaluate the environmental and economic performance of four beef farming systems with different feeding strategies in southern Brazil: grazing on natural pasture (NP); grazing on improved pasture (IP); grazing on natural pasture and crop residues (CR); and grazing on natural pasture and feedlot fattening (FL). Environmental indicators used to compare these farming systems were global warming potential (GWP), fossil energy use, and land occupation per kilogram live weight (LW). Life cycle assessment (LCA) was used to quantify environmental indicators from cradle-to-farm gate. The indicator for economic performance was operating profit per farm. The IP system had lower GWP (18.7 kg CO2 -eq.·kg − 1 LW) and land occupation (37 m 2 ·kg − 1 LW) than other systems, whereas its fossil energy use (19.3 MJ·kg − 1 LW) was higher. CR had the highest operating profit (1, 567, 800 R·farm − 1 ) of the four systems, followed by the IP system (616, 400 R·farm − 1 ). Operating profit in the CR system was mainly from crop production (88%). The GWP of the CR system (26.8 kg CO2 -eq.·kg − 1 LW) was similar to the GWP of the NP system (27.3 kg CO2 -eq.·kg − 1 LW). Operating profit of the FL system (148, 100 R·farm − 1 ) was lower than in the NP system (184, 400 R·farm − 1 ). The outcomes of this research suggest that IP is a promising system to improve GWP, land occupation, and operating profit, whereas CR has the potential to improve economic performance of whole farms in southern Brazil. Highlights: Assessment of beef farming systems with different feeding strategies in Brazil Beef production on natural pasture is most common, and used as a reference. Improved pasture has both better environmental and economic performance. Profit in systems combining beef and soybean production originates from soybeans mainly. Feedlot finishing improves environmental, but not economic performance.